Chondrogenic potential of injectable κ‐carrageenan hydrogel with encapsulated adipose stem cells for cartilage tissue‐engineering applications. (9th January 2013) - Popa, Elena G.; Caridade, Sofia G.; Mano, João F.; Reis, Rui L.; Gomes, Manuela E.
Abstract: Due to the limited self‐repair capacity of cartilage, regenerative medicine therapies for the treatment of cartilage defects must use a significant amount of cells, preferably applied using a hydrogel system that can promise their delivery and functionality at the specific site. This paper discusses the potential use of κ ‐carrageenan hydrogels for the delivery of stem cells obtained from adipose tissue in the treatment of cartilage tissue defects. The developed hydrogels were produced by an ionotropic gelation method and human adipose stem cells (hASCs) were encapsulated in 1.5% w/v κ ‐carrageenan solution at a cell density of 5 × 10 6 cells/ml. The results from the analysis of the cell‐encapsulating hydrogels, cultured for up to 21 days, indicated that κ ‐carrageenan hydrogels support the viability, proliferation and chondrogenic differentiation of hASCs. Additionally, the mechanical analysis demonstrated an increase in stiffness and viscoelastic properties of κ ‐carrageenan gels with their encapsulated cells with increasing time in culture with chondrogenic medium. These results allowed the conclusion that κ ‐carrageenan exhibits properties that enable the in vitro functionality of encapsulated hASCs and thus may provide the basis for new successful approaches for the treatment of cartilage defects. Copyright © 2013 John Wiley & Sons, Ltd.